Al-Qur’an Education Assistance Based on Love Curriculum for Students of Tpq Aikal Sumur Dewa Bengkulu by Pgmi Kkn Students - Masrifa Hidayani; Agustina Putri Utami; Zakiah Balqis; Peby Chattrindo; Suci Indah Lestari; Agita Salsabila (Edumaspul: Jurnal Pendidikan, 2026)
Al-Qur’an education for early childhood is often faced with the challenge of boredom due to approaches that tend to be rigid and solely target-oriented. This community service activity through the Real Work Lecture (KKN) of Madrasah Ibtidaiyah Teacher Education (PGMI) students aims to implement Al-Qur’an education assistance based on the Love Curriculum (Kurikulum Cinta) at TPQ Aikal, Sumur Dewa Village, Bengkulu. The Love Curriculum emphasizes a humanistic, compassionate, fun learning pedagogy centered on children’s psychological comfort. The implementation method uses the Asset-Based Community Development (ABCD) approach to map and optimize the local potential of the TPQ institution. The results of the assistance showed a significant transformation in the students’ intrinsic motivation in reciting, an increase in the speed of understanding makhorijul huruf, and the creation of an inclusive and cheerful classroom atmosphere. Program evaluation using the Societal Impact Index (SII) resulted in an effectiveness score of 94.2% (very high category). The social impact of this program includes increasing trust of student guardians in the existence of TPQ Aikal and the formation of a child-friendly Al-Qur’an learning model draft in Sumur Dewa Village, Bengkulu by Group 14